Effect of anchor shear deformation on the propagation rules of excitation stress waves - Chuanming Li; Chuan Li; Bochao Nie; Qinghua Han; Jianguo Cao (Scientific Reports)
Abstract To address the shear deformation failure resulting from misalignment of rock strata in anchor support, a range of methods, including laboratory tests, numerical simulation, and others, are employed to study the deformation process of anchor rods under shear comprehensively. This approach permits an investigation of the deformation characteristics of the surrounding rock and anchoring agent under shear. Moreover, the propagation characteristics of the stress wave in the anchor rods under shear with varying degrees of deformation have been elucidated. A novel non-destructive testing method for assessing the degree of shear deformation in anchor rods is proposed based on the correlation between the energy evolution law of the stress wave and the degree of anchor deformation. Following experimental verification, it was determined that the average discrepancy between the detection outcomes of the stress wave method and the actual measurement results was minimal and consistent. The findings provide a theoretical foundation for the non-destructive testing of anchor rod shear deformation under on-site support conditions.